Establishment of rapid and non-invasive protocols to identify b-carrying individuals of psalidodon paranae - Goes, Caio Augusto Gomes [UNESP]; De Andrade Silva, Duílio Mazzoni Zerbinato [UNESP]; Utsunomia, Ricardo; Yasui, George Shigueki; Artoni, Roberto Ferreira; Foresti, Fausto [UNESP]; Porto-Foresti, Fábio [UNESP] (FapUNIFESP (SciELO), 2021)
Supernumerary, or B, chromosomes are present in several eukaryotes, including characid fish of the genus Psalidodon. Notably, Psalidodon paranae carries the most studied B chromosome variant, a macro-B chromosome. The origin of this element was determined to be an isochromosome; however, data regarding its inheritance remain unavailable due to methodological barriers such as the lack of an efficient, non-invasive, and rapid protocol for identifying B-carrying individuals that would enable the design of efficient crossing experiments. Thus, in this study, we primarily aimed was to develop two non-invasive and fast (approximately 2 h) methods to identify the presence of B chromosomes in live specimens of P. paranae based on satellite DNA (satDNA) sequences known to be present in this element. The methods include fluorescence in situ hybridization in interphase nuclei and relative gene quantification of satDNAs using quantitative polymerase chain reaction. Our results reveal the efficiency of quickfluorescence in situ hybridization and quantitative polymerase chain reaction for identifying B-carrying individuals using the proposed satDNA sequences and open up new possibilities to study B chromosomes.
Keywords: B chromosomes; Neotropical fishes; Psalidodon; QPCR; Satellite DNA